Electrical Energy of Iron-Air Battery with Carbon Cathodes Using Sea Water Electrolyte - Mardwianta, Benedictus (SENATIK STT Adisutjipto, 2018)
Iron is chosen for the manufacture of air batteries because it is cheap, widely available in nature. One solution currently being developed is the creation of air batteries. This study aims to determine the effect of electrolyte of seawater and the temperature of air that is in direct contact with carbon cathodes and iron anodes of air batteries as a source of electrical energy.The method used in the voltaic cell which is an electrolyte, anode and cathode solution. It is this anode and cathode that causes a reduction and oxidation reaction, as well as an electrolyte as a conduit to produce electrical energy from chemical reactions. The higher the temperature of the air in contact with the battery will reduce the battery's electrical power.The decreasing air density will reduce the amount of air mass, so that the air mass that is in direct contact with the electrode gets less.